Majocchi's granuloma - Case report - Izabel Cristina Soligo Kanaan; Talita Batalha Pires dos Santos; Bernard Kawa Kac; Ariane Molinaro Vaz de Souza; Ana Maria Mosca de Cerqueira (Sociedade Brasileira de Dermatologia, 2015)
We report the case of a three-year-old child who, following long term treatment with topical corticosteroids and their associations for a case of ringworm on the face developed a form of folliculitis known as Majocchi's Granuloma. Treatment with oral Griseofulvin was successful.